Subsequent publication of abstracts presented at the International Association of Paediatric Dentistry meetings - Goran Dahllof (IAPD and Blackwell, 2008)
Presentation of scientific information at international meetings is important for the dissemination of new scientific research. During recent years, there have been increased numbers of scientific societies and meetings as well as numbers of abstracts presented to those meetings. It is often assumed that the information contained in an abstract presentation will subsequently be published in a scientific journal in full-length form. However, previous research has established that less than half of all abstracts are subsequently published in peer-reviewed, indexed journals. A study of abstracts presented to the European Orthodontic Society, the European Organization of Caries Research, and the International Association of Dental Research in1993 showed that 46% of the abstracts were found as published articles